Dakwah Multikultural Islami Menuju Masyakarat Qur’aniala Islam Nusantara - Yasin, Nur Yasin; Aminah, Siti; Ghofur, Abdul (Institut Agama Islam Syarifuddin Lumajang, 2023)
Abstract: Da'wah of Islam must be continued and strengthened. Da'wah should not stop before there is an order to stop preaching. However, this da'wah should not become legitimacy and motivation to act as he pleases without censorship. Da'wah cannot be separated from the spirit of preaching. Such as Islamic da'wah. It has a clear basis. He leaned on the preaching spirit of his predecessors who were polite, full of impressive invitations. Polite preaching, one of which has given birth to Islam Nusantara, a glorious gift from Allah. It is a very distinctive variant. Friendly and peaceful Islam. This da'wah is now being continued by Islam Nusantara as its heir. Dakwah that is thick with the spirit of da'wah, upholds the noble values ​​of al-akhlaq al-karimah to create an Islamic Qur'anic society. Abstrak Dakwah Islam harus terus dilanjutkan dan dikuatkan. Dakwah tidak boleh berhenti sebelum ada komando untuk mengentikan dakwah. Namun dakwah tersebut jangan menjadi legitimasi dan motivasi untuk bersikap sesukanya tanpa sensor. Dakwah tidak bisa dipisahkan dari ruh dakwahnya. Semisal dakwah Islam. Ia memiliki dasar yang gamblang. Ia bersandar pada ruh dakwah para pendahulu yang santun, penuh ajakan yang mengesankan. Dakwah yang santun, salah satunya telah melahirkan Islam Nusantara, anugerah Allah yang gemilang. Ia menjadi varian tersendiri yang sangat khas. Islam yang ramah dan damai. Dakwah tersebut kini diteruskan oleh Islam Nusantara sebagai pewarisnya. Dakwah yang kental dengan ruh dakwah, menjunjung tinggi nilai-nilai agung al-akhlaq al-karimah untuk mewujudkan masyarakat yang Islami Qur’ani.